Redirecting the incredulous stare: contemporary metaphysical complacency and the flanking manoeuvre of developmental scepticism - Schellenberg, J. L. (Religious studies, 2026)
With development understood as improving change, and working at the macroscale or species level, I sketch the conceptual background for a new, developmental form of scepticism. Then I use developmental scepticism to critique a proposition that functions as a presupposition of the popular contemporary rejection of unconventional metaphysical propositions (MUPs) and specifically of panpsychism: namely, that we have experienced enough relevant development as a species to make it reasonable for the community of enquiry to treat such ideas as obviously false. Finally, I briefly suggest a possible step beyond developmental scepticism toward a more general orientation in enquiry which might naturally follow such scepticism once its motivating ideas are absorbed.